The androgen receptor induces a distinct transcriptional program in castration-resistant prostate cancer in man - Sharma, Naomi L; Massie, Charlie E; Ramos-Montoya, Antonio; Zecchini, Vincent; Scott, Helen E; Lamb, Alastair D; MacArthur, Stewart; Stark, Rory; Warren, Anne Y; Mills, Ian G; Neal, David E (Cancer cell, 2013)
The androgen receptor (AR) regulates prostate cell growth in man, and prostate cancer is the commonest cancer in men in the UK. We present a comprehensive analysis of AR binding sites in human prostate cancer tissues, including castrate-resistant prostate cancer (CRPC). We identified thousands of AR binding sites in CRPC tissue, most of which were not identified in PC cell lines. Many adjacent genes showed AR regulation in xenografts but not in cultured LNCaPs, demonstrating an in-vivo-restricted set of AR-regulated genes. Functional studies support a model of altered signaling in vivo that directs AR binding. We identified a 16 gene signature that outperformed a larger in-vitro-derived signature in clinical data sets, showing the importance of persistent AR signaling in CRPC.